"Legal Gentlemen Appointed by the Federal Government": the Canadian State, the Citizens' Committee of 1000, and Winnipeg's Seditious Conspiracy Trials of 1919-1920 - Mitchell, Tom (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2004)
Abstract In the fall and winter of 1919-1920, in response to vigorous lobbying by A.J. Andrews and others on behalf of the Citizens’ Committee of 1000, the Canadian state, through Orders in Council in 1919 and 1920, became the paymaster for a private prosecution of the Winnipeg strike leadership charged at the end of the strike with seditious conspiracy. The prosecution was initiated under provisions of the Criminal Code that allowed for prosecutions by private citizens or organizations, subject to the consent of the Attorney General of Manitoba. The federal government paid Alfred J. Andrews and his associates in the Citizens’ Committee fees for services rendered during the strike, when, as leading figures in the Committee, they led the campaign against Winnipeg’s working-class revolt. The Department of Justice also paid $12,332.00 to the Winnipeg based McDonald Detective Agency for work associated with the prosecution. This federal largesse allowed Andrews to secure two juries almost certainly tainted by pre-trial investigations ordered by Andrews. The unity of purpose forged by Winnipeg’s business elite and the federal state illuminates the tendency of the liberal state and capital to forge a common front against perceived threats to the status quo in moments of extremis.